The Role of Technology Acceptance Model Theory and the Relationship with Hifz Mal in the Phenomences of Using E-Money in the Milenial Era - Yumasepta Rizky Hapsari; Darwanto Darwanto; Edy Yusuf Agung Gunanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
This research aims to see the role of the Technology Acceptance Model theory that can influence the millennial generation in using e-money and its relationship with hifz mal. The basic variables are ease and usefulness, and also three other variables, namely security, trust and experience. The research model was empirically tested using a data collection method through questionnaires for millennial generation of e-money users, namely students of the Faculty of Economics and Business, Diponegoro University using multiple linear regression analysis techniques using the SPSS 22 application. The results showed that usefulness and trust variables have a positive and significant effect on the use of e-money. Meanwhile, convenience, security and experience do not play a role in influencing the millennial generation in using e-money. The connection with hifz mal is that the use of e-money provides convenience and benefits for its users while providing security guarantees, so that Muslim users of electronic money avoid things that are not in accordance with the Islamic economic system.